Effects of multi-site non-invasive brain stimulation on cognitive impairment after stroke: a systematic review and meta-analysis - Heling Wang; Di Zhang; Xu Wang; Qixin Ding; Shenhong Ma; Qiaohua Han; Yuefang Li; Tianshu Li; Ying Li; Wanyue Li; Weisheng Zhuang; Weisheng Zhuang (Frontiers in Human Neuroscience)
ObjectivePost-stroke cognitive impairment (PSCI) is one of the core symptoms following a stroke, which severely affects the prognosis of patients. This systematic review and meta-analysis aim to explore the effectiveness and safety of multi-site non-invasive brain stimulation (MS-NIBS) in enhancing the cognitive function of PSCI patients.MethodsA comprehensive search was conducted in multiple databases, including MEDLINE (PubMed), Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data, VIP Database for Chinese Technical Periodicals, and Chinese Biomedical Literature Database (CBM). The search was performed up to 18 January 2025. The inclusion criteria for this meta-analysis were randomized controlled trials (RCTs) of MS-NIBS for PSCI. The primary outcome measure was the change in the global cognitive scale, while the secondary outcomes focused on improvements in attention, memory, visuospatial perception, and activities of daily living. The Cochrane Risk of Bias Tool was used to assess the quality of each eligible study. Meta-analysis and bias analysis were performed using RevMan (Version 5.3).ResultsA total of 6 RCTs involving 416 samples were included in this paper. The findings from the primary outcomes revealed that the MS-NIBS group had significantly higher scores on the Montreal Cognitive Assessment (MOCA) of the cognitive composite scale (MD = 1.84, 95% CI = 1.21–2.48, p < 0.00001, I2 = 36%) compared to the single-site non-invasive brain stimulation (SS-NIBS) group. As for the secondary outcome measures, as shown by the Digit Span Test (DST) forward recall (MD = 0.94, 95% CI = −1.11 to 2.98, p = 0.37, I2 = 97%), DST backward recall (MD = 0.03, 95% CI = −0.24 to 0.29, p = 0.85, I2 = 0%), Clock Drawing Test (CDT) (MD = 1.65, 95% CI = 0.77–2.53, p = 0.0003, I2 = 54%), Trail Making Test (TMT) (MD = 4.2, 95% CI = 2.71–5.69, p < 0.00001, I2 = 14%), and Modified Barthel Index (MBI) for activities of daily living assessment (MD = 3.71, 95% CI = −4.77 to 12.20, p = 0.39, I2 = 75%), the MS-NIBS group showed improvements in visuospatial and trail-making test abilities. Subgroup analysis of the main outcome demonstrated that multi-site transcranial magnetic stimulation (MS-TMS) (MD = 2.1, 95% CI = 1.38–2.81, p < 0.00001, I2 = 48%) and the combined treatment of TMS and transcranial direct current stimulation (tDCS) (MD = 1.91, 95% CI = 0.81–3.01, p = 0.0007, I2 = 0%) exhibited superior efficacy compared to SS-NIBS.ConclusionThis meta-analysis provides evidence supporting that MS-NIBS, as an emerging neuromodulatory tool, is superior to SS-NIBS in improving the overall cognitive abilities of stroke patients. However, given the limited number of included studies, it is necessary to further validate these findings through large-scale, multi-center, double-blind, and high-quality RCTs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42025640015.